1975
DOI: 10.1139/m75-221
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the immunizing activity of ribosomal fractions isolated from Mycobacterium tuberculosis var. bovis strain BCG

Abstract: Levels of antituberculous immunity similar to those induced by live BCG vaccine were detected in CF1 mice immunized with ribosomal fractions isolated from Mycobacterium tuberculosis var. bovis, strain BCG, and challenged 3 weeks later with the virulent H37Rv strain of Mycobacterium tuberculosis var. hominis. The activity of the crude ribosomal preparations was found to be a function of the immunizing doses and the immunity induced by 1.0-mg doses remained at the same high level after 4 weeks of storage at 4 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1976
1976
1989
1989

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The carbohydrate-containing substances of ~ibosimal' fractions were injected in incomplete Freund's the H37Ra ribosomal fractions were purified by affinity adjuvant, all emulsions being prepared as previously described chromatography on concanavalin A -Sepharose 4B, and (Portelance et al 1975). Experimental animals were injected the formation of complexes between these substances i.p.…”
Section: Estimate Of Immunizing Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…The carbohydrate-containing substances of ~ibosimal' fractions were injected in incomplete Freund's the H37Ra ribosomal fractions were purified by affinity adjuvant, all emulsions being prepared as previously described chromatography on concanavalin A -Sepharose 4B, and (Portelance et al 1975). Experimental animals were injected the formation of complexes between these substances i.p.…”
Section: Estimate Of Immunizing Activitymentioning
confidence: 99%
“…These suspensions were samples were diluted at 4 mg/mL in the sample buffer used to prepare the ribosomal fractions as previously described (Laernrnli 1970) and heated in a boiling water bath for 2 min. (Portelance et al 1975).…”
Section: Preparation Of Ribosomal Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Youmans and Youmans (29) reported that the isolated active fraction of M. tuberculosis is a double-stranded RNA, no one has reported similar results on mycobacteria. Portelance et al (19,20) suggested that polysaccharide or RNA-polysaccharide complexes may play an important role in the induction of immunity against tuberculosis. However, these investigators did not identify the hypothetic polysaccharide involved.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest that in spite of the evidence that BCG vaccination protects by reducing bacillemia (13,17), data indicating that experimental vaccines are protective has generally been obtained with animal models in which the animals were challenged intravenously or intraperitoneally, routes which prevent the investigator from measuring the extent to which vaccination inhibits bacillemia (4, 26,51).…”
Section: Contribution Of Animal Models To Vaccine Developmentmentioning
confidence: 99%